Analisis Pola Komunikasi Guru dengan Peserta Didik pada Pembelajaran Sosiologi di SMA Negeri 2 Sungai Raya - Indera Gust Mou Triliun (Indo Publishing, 2026)
This research aims to describe the communication patterns used by teachers in Sociology lessons for class XI IPS III at SMA Negeri 2 Sungai Raya, Kubu Raya Regency, and to identify the factors influencing the effectiveness of classroom communication. Utilizing a descriptive qualitative approach, this study collected primary data through direct observation, in-depth interviews with teachers and students, and documentation including photos and questionnaires. The data collection process involved researchers observing the interaction dynamics between teachers and students. The results indicate that teachers tend to rely on primary communication patterns using the direct lecture method, characterized by verbal delivery supported by body language and nonverbal expressions. The use of secondary communication patterns, such as digital aids, remains very limited. Furthermore, linear communication patterns are evident when teachers provide instructions to students. The findings reveal that students, particularly those in the middle and back rows, frequently lose focus due to distractions from mobile phone usage and a lack of two-way interaction. This study also identifies that effective classroom management, the teacher's ability to adapt communication strategies, and the implementation of varied learning media are key factors in enhancing the effectiveness of the learning process. Based on these findings, it is recommended to increase the integration of technology and interactive learning activities to create a more conducive and participatory learning environment. The results of this study are expected to serve as input for developing communication strategies in education, specifically in Sociology instruction